Twelve Recommendations for Advancing Marine Conservation in European and Contiguous Seas - Katsanevakis, Stelios; Coll, Marta; Fraschetti, Simonetta; Giakoumi, Sylvaine; Goldsborough, David; Mačić, Vesna; Mackelworth, Peter; Rilov, Gil; Stelzenmüller, Vanessa; Albano, Paolo G.; Bates, Amanda E.; Bevilacqua, Stanislao; et al. (Frontiers in Marine Science, 2020)
Like most ocean regions today, the European and contiguous seas experience cumulative impacts from local human activities and global pressures. They are largely in poor environmental condition with deteriorating trends. Despite several success stories, European policies for marine conservation fall short of being effective. Acknowledging the challenges for marine conservation, a four-year multi-national network, MarCons, supported collaborative marine conservation efforts to bridge the gap between science, management and policy, aiming to contribute in reversing present negative trends. By consolidating a large network of more than 100 scientists from 26 countries, and conducting a series of workshops over four years (2016-2020), MarCons analysed challenges, opportunities and obstacles for advancing marine conservation in the European and contiguous seas. Here, we synthesize the major issues that emerged from this analysis and make 12 key recommendations for policy makers, marine managers, and researchers. To increase the effectiveness of marine conservation planning, we recommend (1) designing coherent networks of marine protected areas (MPAs) in the framework of marine spatial planning (MSP) and applying systematic conservation planning principles, including re-evaluation of existing management zones, (2) designing MPA networks within a broader transboundary planning framework, and (3) implementing integrated land-freshwater-sea approaches. To address inadequate or poorly informed management, we recommend (4) developing and implementing adaptive management plans in all sites of the Natura 2000 European conservation network and revising the Natura 2000 framework, (5) embedding and implementing cumulative effects assessments into a risk management process and making them operational, and (6) promoting actions to reach ‘good environmental status’ in all European waters. To account for global change in conservation planning and management, we further recommend (7) developing conservation strategies to address the impacts of global change, and (8) incorporating biological invasions in conservation plans and prioritizing management actions to control invasive species. Finally, to improve current practices that may compromise the effectiveness of conservation actions, we recommend (9) reinforcing the collection of high-quality open-access data, (10) improving mechanisms for public participation in MPA planning and management, (11) prioritizing conservation goals in full collaboration with stakeholders, and (12) addressing gender inequality in marine sciences and conservation.